Efficacy and Safety of Abatacept in Lupus Nephritis: A Twelve‐Month, Randomized, Double‐Blind Study - Furie, Richard; Nicholls, Kathy; Cheng, Tien‐Tsai; Houssiau, Frederic; Burgos‐Vargas, Ruben; Chen, Shun‐Le; Hillson, Jan L.; Meadows‐Shropshire, Stephanie; Kinaszczuk, Michael; Merrill, Joan T. (Arthritis & rheumatology (Hoboken, N.J.), 2014)
Objective To compare the efficacy and safety of intravenous (IV) abatacept, a selective T cell costimulation modulator, versus placebo for the treatment of active class III or IV lupus nephritis, when used on a background of mycophenolate mofetil and glucocorticoids. Methods This was a 12‐month, randomized, phase II/III, multicenter, international, double‐blind study. A total of 298 patients were treated in 1 of 3 IV treatment arms: placebo, abatacept at the standard weight‐tiered dose (approximating 10 mg/kg), or abatacept at 30 mg/kg for 3 months, followed by the standard weight‐tiered dose (abatacept 30/10). The primary end point, time to confirmed complete response, was a composite measure that required maintenance of glomerular filtration rate, minimal proteinuria, and inactive urinary sediment over the 52‐week treatment period. Results There were no differences among treatment arms in the time to confirmed complete response or in the proportion of subjects with confirmed complete response following 52 weeks of treatment. Treatment with abatacept was associated with greater improvements from baseline in anti–double‐stranded DNA antibody, C3, and C4 levels. Among 122 patients with nephrotic‐range proteinuria, treatment with abatacept resulted in an ∼20–30% greater reduction in mean urinary protein‐to‐creatinine ratio compared with placebo. Abatacept was well tolerated; rates of deaths, serious adverse events, and serious infections were similar across treatment arms. Gastroenteritis and herpes zoster occurred more frequently with abatacept treatment. Conclusion Although the primary end point was not met, abatacept showed evidence of biologic activity and was well tolerated in patients with active class III or IV lupus nephritis.